The Structure of Electricity Consumption and its Utilisation Efficiency in the European Transition Countries - Milan Ivanović; Damir Blažević; Hrvoje Glavaš (International Journal of Electrical and Computer Engineering Systems, 2010)
The paper considers end-use electricity consumption and efficiency trends in transition countries, i.e. ten former socialist states that are now new EU members, and the Republic of Croatia as a candidate country. For the last twenty years, transition countries are in the process of changing their social, economic and political structures with considerable influence on the electricity sector. In these former socialist countries, due to a planned economy, the energy sector has been significantly irrational. The paper analyzes efficiency of energy consumption on a national level, electricity intensive branches and especially electricity consumption in the sector of services and households. Efficiency of electricity consumption in transition countries is analyzed and compared with the same indicators of the fourteen developed European countries. Furthermore, the structure of electricity consumption and its utilization efficiency in transition countries and Croatia is presented. Finally, techno-economical solutions are proposed.